Prthas inmunization digest - Parthasarathy, A. (New Delhi : Jaypee Brothers Medical Publishers, 2011)
An updated and revised book with detailed information on various aspects of immunization. Practical guidelines are incorporated on Vaccine Administration and Safe Injection Practices. Diagrams' showing administering multiple vaccines at the same sitting provides a visual guide.
1.Inmunization: the way forward 2. Basic of caccinology 3. Inmunization schedules 4.Vaccines, immunization in especial clinical 5. Determination of the heart rate y otros
Keywords: Vacunas